2010
DOI: 10.1007/s10646-010-0499-7
|View full text |Cite
|
Sign up to set email alerts
|

Microcystis toxigenic strains in urban lakes: a case of study in Mexico City

Abstract: Microcystis is a bloom-forming, common cyanobacterium in urban lakes of Mexico City. To assess the presence of potentially cyanotoxin-producing Microcystis, molecular techniques were applied and acute toxicity bioassays were performed with Daphnia magna neonates exposed to cyanobacterial crude extracts. Toxigenic potential of isolated strains was inferred by amplifying the mcyA-Cd genes and their identity as Microcystis was confirmed through the 16S rDNA and phycocyanin operon amplification. Microcystins synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…Only recently, however, have MCYSTs been identified in Mexican freshwater systems. In addition to a previous report in the scientific literature of MC‐LR 31 in a reservoir in Valle de Bravo, two very recent studies 32, 33 have identified MCYSTs or MCYST‐producing strains of Microcystis in several such systems, including natural and urban lakes, additional reservoirs, and channels. Concentrations of particulate MCYST in Lago de Patzcuaro are low to intermediate to levels found in other freshwater systems, and lower than levels measured in other Mexican lakes.…”
Section: Discussionmentioning
confidence: 81%
“…Only recently, however, have MCYSTs been identified in Mexican freshwater systems. In addition to a previous report in the scientific literature of MC‐LR 31 in a reservoir in Valle de Bravo, two very recent studies 32, 33 have identified MCYSTs or MCYST‐producing strains of Microcystis in several such systems, including natural and urban lakes, additional reservoirs, and channels. Concentrations of particulate MCYST in Lago de Patzcuaro are low to intermediate to levels found in other freshwater systems, and lower than levels measured in other Mexican lakes.…”
Section: Discussionmentioning
confidence: 81%
“…G. gracilis is a filter feeder and omnivorous fish that lives in remnant water bodies of Central Mexico that sustain contamination with large amounts of nutrients and organic matter. Recent studies report high concentrations of MCs in lakes in Chapultepec Park, in addition to diverse strains that produce these cyanotoxins (Arzate‐Cárdenas et al, ). In view of the threatened status of this species and the lack of information on permissible levels of MCs in freshwater systems in Mexico, the present study assessed PP activity; LDH and ADH metabolism; ROS formation normalO2, H 2 O 2 ); oxidative stress measured as thiobarbituric acid reactive substances (TBARS), lipid hydroperoxides (ROOHs) and protein oxidation (RCO); and antioxidant defense as determined by the activity of the enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx), in the livers of G. gracilis exposed to different cell densities of the MC‐producing strain Microcystis aeruginosa LB85 under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Later, blooms were reported in the Valle de Bravo reservoir (Ramírez García et al, 2002) and a eutrophic crater lake in Los Tuxtlas (Vázquez et al, 2005); in both cases, blooms were recorded in spring and summer, with a decline in biomass in surface waters during winter. The occurrence of microcystins in eutrophic reservoirs and urban lakes in Mexico has also been reported, with microcystins concentrations exceeding the WHO recommended limit (1 µg L -1 ) (Arzate-Cárdenas et al, 2010;Vasconcelos et al, 2010;Pineda-Mendoza et al, 2012); M. aeruginosa and other Microcystis species dominated the phytoplankton community of these reservoirs and urban lakes. Therefore, monitoring the presence and abundance of M. aeruginosa in lakes and reservoirs in Mexico from which the water is used for agricultural, recreational and human consumption purposes is crucial to avoid health risks, especially if these waterbodies are prone to eutrophication.…”
Section: Introductionmentioning
confidence: 81%
“…A high incidence of cyanobacterial blooms has been observed in tropical regions of Africa, America, Asia and Australia (Frias et al, 2006;Haande et al, 2007;Arzate-Cárdenas et al, 2010;Mowe et al, 2014;Ninio et al, 2020). In Mexico, the dominance of M. aeruginosa was reported for the first time in an artificial reservoir of Mexico City (Alcocer et al, 1998), and Lake Atezca, a subtropical monomictic lake (Dıáz-Pardo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%